KORELASI DAKWAH KYAI DALAM PENGAJIAN KITAB AL-KABA’IR DENGAN TINGKAT KESADARAN SANTRI PADA BAHAYA DOSA BESAR - Mufidzati, Khumairo; Masruroh, Sayidah Afyatul (Universitas Hasyim Asy'ari, 2023)
Da’wa, in general, is an activity of inviting or exhorting towards good deeds and abstaining from bad deeds, through preaching delivered by a religious teacher (kyai) during the study of the book Al-Kaba'ir. This direct preaching enhances the knowledge, understanding, and awareness of the students (santri) of Pondok Pesantren Nurul Ilmi Wal Fikri Tebuireng Jombang regarding the dangers of major sins, thereby encouraging their attitudes and behaviors to avoid committing major sins and developing a sense of consciousness within themselves. The aim of this research is to determine the correlation between the kyai's preaching in the study of the book Al-Kaba'ir and the level of consciousness among the students regarding the dangers of major sins at Nurul Ilmi Wal Fikri Tebuireng Jombang Islamic boarding school. This study employs a quantitative method, specifically correlational research. It can be concluded from this research that there is a significant, strong, and positive correlation between the kyai's preaching in the study of the book Al-Kaba'ir and the level of consciousness among the students regarding the dangers of major sins. This is evidenced by the assessments of the respondents (students of Pondok Pesantren Nurul Ilmi Wal Fikri Tebuireng Jombang). It is also supported by the results of the Spearman rank correlation test, which yielded a Sig value of 0.000 < 0.05. Therefore, the alternative hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected, indicating that there is a correlation (relationship) between the kyai's preaching in the study of the book Al-Kaba'ir and the level of consciousness among the students regarding the dangers of major sins. The obtained correlation coefficient is 0.697.